Performance in B2B sales: An explanation of how channel management and communication influence a firm's performance - Günther Maier (Naše gospodarstvo / Our Economy, 2021)
Communication between seller and buyer is done through multiple channels. There are multiple ways to use technical media and channel selection to create more information, but does this lead to a better performance of a firm? Research on the impact of different marketing channels in the industry regarding performance factors remains scarce. The performance of a firm is the most significant factor and will be monitored through different attributes. The purpose of this paper is to review the drivers of a sales process in terms of sales cycles, channels and communication in relation to it's effect on performance. Beyond the characteristics of sales the review delineates the changes from the past to the present. The contribution of this review is to understand the various capabilities in channel management and communication that can be adapted to the sales process and increase a firm's performance.
Keywords: M16; M31; L22; L25; 330; Channel management; communication; sales performance; sales cycle; industrial marketing